Incorporating Local Culture in English Language Teaching for Papuan Junior High School Students - Abel Yohanis Romrome; Ouda Teda Ena (Journal of English Education and Teaching, 2022)
Local culture is a crucial aspect in human life. Local culture relates to the way of human life such as thinking, feeling, and acting. It is undeniable that local culture could be used in the academic context as the medium in learning English. By using local culture, students will be able to empower their ability in thinking, speaking, and writing. Therefore, the teachers are required to design the learning process by providing local culture contents or materials that the students are familiar with. This research aimed to analyse whether Junior High School's teachers have implemented three ways in a local culture based on teaching English which was proposed by Goldberg and to find out whether the students feel more enthusiastic in learning by using local culture content. Besides that, this study was to investigate and measure the influence of local culture on students’ skills before and after using local culture contents in learning English. The data of research were collected from two Junior High Schools in Timika-Papua, Indonesia. They were SMP N 2 and SMP N 8. The method of this research was both quantitative and qualitative. In gaining the data, the researcher distributed the questionnaire to 107 students and interviewed two teachers and two students. After that, the researcher collected the data, identified, and analysed it by using SPSS 26.0. The findings revealed that Papuan English teacher have used local culture contents in providing the English materials for the students. On the other hand, students’ skills can be improved to be better by using local culture contents in learning English.